Unexpected variation of human molar size patterns. Issue 161 (December 2021) - Boughner, Julia C.; Marchiori, Denver F.; Packota, Garnet V.
Abstract: A tenet of mammalian, including primate dental evolution, is the Inhibitory Cascade Model, where first molar (M1) size predicts in a linear cline the size and onset time of the second (M2) and third (M3) molars: a larger M1 portends a progressively smaller and later-developing M2 and M3. In contemporary modern Homo sapiens, later-developing M3s are less likely to erupt properly. The Inhibitory Cascade Model is also used to predict molar sizes of extinct taxa, including fossil Homo . The extent to which Inhibitory Cascade Model predictions hold in contemporary H. sapiens molars is unclear, including whether this tenet informs about molar initiation, development, and eruption. We tested these questions here. In our radiographic sample of 323 oral quadrants and molar rows from contemporary humans based on mesiodistal crown lengths, we observed the distribution of molar proportions with a central tendency around parity (M1 = M2 = M3) that parsed into 13 distinct molar size ratio patterns. These patterns presented at different frequencies (e.g., M1 > M2 > M3 in about one-third of cases) that reflected whether the molar row was located in the maxilla or mandible and included both linear (e.g., M1 < M2 < M3) and nonlinear molar size ratio progressions (e.g., M1 > M2 < M3). Up to four patterns were found in the same subject's mouth. Lastly, M1 size alone does not predict M3 size, developmental timing, or eruption; rather, M2 size is integral to predicting M3 size. Our study indicates that human molar size is genetically 'softwired' and sensitive to factors local to the human upper jaw vs. lower jaw. The lack of a single stereotypical molar size ratio for contemporary H. sapiens suggests that predictions of fossil H. sapiens molar sizes using the Inhibitory Cascade Model must be made with caution. Highlights: In humans, M1 size alone does not predict M3 size, initiation time or eruption. Human M1, M2, and M3 sizes are highly variable, even within the same person's mouth. Variation in molar size is linked to whether molars are in the upper or lower jaw. Contemporary human molars do not show just one stereotypical size pattern. Lack of a single 'human' pattern may confound identifying fossil hominine molars.